Respuesta :
Answer:
y = 5x - 23
Step-by-step explanation:
Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.
First, subtract 10x from both sides:
10x (-10x) - 2y = 46 (-10x)
-2y = -10x + 46
Next, divide -2 from all terms in the equation:
(-2y)/-2 = (-10x + 46)/-2
y = (-10x)/-2 + (46)/-2
y = 5x - 23
y = 5x - 23 is your answer.
~
Answer:
y= 5x-23
Step-by-step explanation:
10x-2y =46
10x-10x-2y =46-10x
-2y= 46-10x
-2y/-2= 46-10x/-2
y= 5x-23